AKSES KONTROL KOTAK KUNCI RUANG KELAS BERBASIS SMARTPHONE ANDROID - Muhammad Arifin; Egi Fazar Firrizqi; Abdullah Sani (JURNAL INTEGRASI, 2019)
Recently, many smartphones have applied Android as their operating system. Operating system Android has many advantages such as it is used in many kind of smartphone, cheap, and so on. Joining operating system Android and microcontroller system will have more advantages and applications. One of its applications is as smart storage box for keys. The data of key’s user can be monitored easily using this smart storage box. In this research was carried out some examinations for smart storage box including application, examining application against hardware, and the data display in website. The results of function examinations show that smart storage box for keys worked successfully and monitoring data in website can also be conducted well with real time.